Toward a consensus nomenclature for ghrelin, its non-acylated form, liver expressed antimicrobial peptide 2 and growth hormone secretagogue receptor - Perello, Mario (2022)
The stomach-derived octanoylated peptide ghrelin was discovered in 1999 and recognized as an endogenous agonist of the growth hormone secretagogue receptor (GHSR). Subsequently, ghrelin has been shown to play key roles in controlling not only growth hormone secretion, but also a variety of other physiological functions including, but not limited to, food intake, reward-related behaviors, glucose homeostasis and gastrointestinal tract motility. Importantly, a non-acylated form of ghrelin, desacyl-ghrelin, can also be detected in biological samples. Desacyl-ghrelin, however, does not bind to GHSR at physiological levels, and its physiological role has remained less well-characterized than that of ghrelin. Ghrelin and desacyl-ghrelin are currently referred to in the literature using many different terms, highlighting the need for a consistent nomenclature. The variability of terms used to designate ghrelin can lead not only to confusion, but also to miscommunication, especially for those who are less familiar with the ghrelin literature. Thus, we conducted a survey among experts who have contributed to the ghrelin literature aiming to identify whether a consensus may be reached. Based on the results of this consensus, we propose using the terms “ghrelin” and “desacyl-ghrelin” to refer to the hormone itself and its non-acylated form, respectively. Based on the results of this consensus, we further propose using the terms “GHSR” for the receptor, and “LEAP2” for liver-expressed antimicrobial peptide 2, a recently recognized endogenous GHSR antagonist/inverse agonist.